1983
DOI: 10.1071/bi9830487
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Pyruvate and Citrate in Lactobacilli

Abstract: Lactobacillus acidophilus, L. bulgaricus, L. casei, L. delbrueckii, L. lactis and L. plantarum contained a pyruvate oxidase for the oxidation of pyruvate to acetyl phosphate and acetate. The presence of an acetate kinase converted the acetyl phosphate to acetate. L. casei and L. plantarum produced lactate and acetoin, in addition to acetate, under the conditions used while L. casei also produced diacetyL L. casei and L. plantarum were the only species to utilize citrate. L. helveticus and L. helveticus subsp. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 21 publications
4
45
0
1
Order By: Relevance
“…Such a coupling was invoked to explain a high level of acetate production in Lactococcus lactis when the NADH oxidase was overexpressed (35). Although an NADH oxidase activity was clearly induced at similar levels in both Lp80 and the PoxBdeficient strain under aerobic conditions, we were unable to detect any PDH activity under the different growth conditions, confirming previous observations that a POX enzyme(s) plays the major role in acetate production under aerobic conditions (6,18,30; data not shown).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Such a coupling was invoked to explain a high level of acetate production in Lactococcus lactis when the NADH oxidase was overexpressed (35). Although an NADH oxidase activity was clearly induced at similar levels in both Lp80 and the PoxBdeficient strain under aerobic conditions, we were unable to detect any PDH activity under the different growth conditions, confirming previous observations that a POX enzyme(s) plays the major role in acetate production under aerobic conditions (6,18,30; data not shown).…”
Section: Discussionsupporting
confidence: 48%
“…This pathway is thought to be mainly active under aerobic conditions since PDH is strongly inhibited under anaerobic conditions by the relatively high NADH level (3). Although putative pdh genes were recently identified in the genome sequence, it was reported that L. plantarum had no detectable PDH activity under various growth conditions (6,18,25,30). Previous physiological studies of L. plantarum indicated that acetate production is maximal under aerobic conditions with glucose limitation.…”
mentioning
confidence: 99%
“…In the presence of inorganic phosphate, the thiamine diphosphate (ThDP)-dependent APF-POX catalyzes the oxidative decarboxylation of pyruvate to acetylϳP, carbon dioxide, and hydrogen peroxide (Fig. 9A) (188,315,402,403,444). In S. pneumoniae, ACP-POX appears responsible for formation of the majority of the acetylϳP, despite the presence of both ACK and PTA.…”
Section: Other Acetylϳp-forming Enzymesmentioning
confidence: 99%
“…Pyruvate oxidases can be divided into two classes: the acetate formers such as POXB of E. coli and the acetylϳP-formers (APF-POX [EC 1.2.3.3]) found in diverse lactobacilli, Pediococcus pseudomonas, and S. pneumoniae (49,188,315,402,403,419). In the presence of inorganic phosphate, the thiamine diphosphate (ThDP)-dependent APF-POX catalyzes the oxidative decarboxylation of pyruvate to acetylϳP, carbon dioxide, and hydrogen peroxide (Fig.…”
Section: Other Acetylϳp-forming Enzymesmentioning
confidence: 99%
“…Rhee et Park (1980) ont montré que Laetobaeillus bulgarieus en culture continue anaérobie avec limitation de glucose passe à un système hétérofermen-taire à la suite d'une augmentation du pH du milieu; dans un environnement alcalin, la biosynthèse de la lactate deshydrogé-nase diminue, et les enzymes du système hétérofermentaire (pyruvate formate lyase, acétate kinase, aldéhyde deshydrogénase et phosphotransacétylase) sont activés. Lloyd et al (1978), Hickey et al (1983) montrent que l'oxydation du pyruvate en Thomas (1987) propose deux mécanismes pour la formation d'acétate dans les fromages; l'un oxygène dépendant avec comme substrat le lactate, l'autre oxygène indépendant avec comme substrat le citrate. Tseng et Montville (1990) constatent des changements d'activités enzymatiques dans des cultures aérobies comparativement aux cultures anaérobies, ainsi que des effets en relation avec des variations de pH.…”
Section: Déterminations Enzymatiquesunclassified